Effect of simulated rains on persistent toxicity of oxydemeton-methyl to mustard aphid (Lipaphis erysimi) on mustard (Brassica juncea) crop - YADAV, G S; CHAUHAN, R; ROHILLA, H R (The Indian Journal of Agricultural Sciences, 2013)
Effect of simulated rains of 0,2,4, 6, 10 and 15 mm done by knapsack sprayer at 0, 2, 4, 8, 12, 24, 48 and 72 hr afteroxydemeton.methyl 0.025% spray on its persistent toxicity to Lipaphis elysimi (Kalt.) infesting 'RH 30' mustard, Brassica juncea (L.) Czem and Coss crop was studied during 1992-93 and 1993-94. Ten apterous adult aphids were released on potted mustard plant leafat 0, 1,3,5,7,10 and 15 days after insecticidal spray followed by simulated rain and later enclosed in a cage. Aphid mortality was recorded 24 hr after each release. The aphid mortality decreased with increasing rain level. The persistent toxicity of oxydemeton-methyl in rain control (no rain but insecticidal spray) was 900 as against 698, 624, 632,599 and 414 in sets receiving 2, 4, 6,10 and IS nun rain respectively during 1992-93. During 199394 persistent toxicities were 805 in rain control and 610, 619, 593,590 and 424 in differentrainIevels. Rain occurring upto 12 hr after oxydemeton-methyl spray brought much reduction in persistent toxicity as compared to those occurring 24, 48 and 72 ht after the spray. If rain of 15 mm occurs 48 hr after oxydemeton-methyl spray than there is no need of its reapplication.